Answer:
m + s = 30
2m + 6s = 100
Step-by-step explanation:
took the test
<span>1) Write the point-slope form of the equation of the horizontal line that passes through the point (2, 1). y = 1/2x
2)Write the point-slope form of the equation of the line that passes through the points (6, -9) and (7, 1).
m = (-9 - 1) / (6 - 7) = -10/-1 = 10
y + 9 = 10 (x - 6)
y = 10x - 69
3) A line passes through the point (-6, 6) and (-6, 2). In two or more complete sentences, explain why it is not possible to write the equation of the given line in the traditional version of the point-slope form of a line.
4)Write the point-slope form of the equation of the line that passes through the points (-3, 5) and (-1, 4).
m = (5 - 4) / (-3 - -1) = 1/-2
y - 5 = (-1/2) (x +3)
y = (-1/2)x + 7/2
5) Write the point-slope form of the equation of the line that passes through the points (6, 6) and (-6, 1).
m = (6-1)/(6 - -6) = 5 / 12
y - 6 = (5/12) (x-6)
y = (5/12)x + 17 / 2
6) Write the point-slope form of the equation of the line that passes through the points (-8, 2) and (1, -4).
m = (2 - -4) / (-8 -1) = 6 / -7
y - 2 = (-6/7) (x + 8)
y = (-6/7)x - 50 / 7
7) Write the point-slope form of the equation of the line that passes through the points (5, -9) and (-6, 1).
m = (-9 - 1) / (5 - -6) = -10 / 11
y + 9 = (-10 / 11) (x - 5)
y = (-10 / 11)x -49/11
</span>
Answer:
Step-by-step explanation:
![\left|x+6\right|=\left|x-12\right|\\\\\mathrm{For\:each\:absolute\:find\:positive\:and\:negative\:intervals}\\ \\\mathrm{For\:}x](https://tex.z-dn.net/?f=%5Cleft%7Cx%2B6%5Cright%7C%3D%5Cleft%7Cx-12%5Cright%7C%5C%5C%5C%5C%5Cmathrm%7BFor%5C%3Aeach%5C%3Aabsolute%5C%3Afind%5C%3Apositive%5C%3Aand%5C%3Anegative%5C%3Aintervals%7D%5C%5C%20%5C%5C%5Cmathrm%7BFor%5C%3A%7Dx%3C-6%3A%5Cquad%20%5Cmathrm%7BNo%5C%3ASolution%7D%5C%5C%5C%5C%5Cmathrm%7BFor%5C%3A%7D-6%5Cle%20%5C%3Ax%3C12%3A%5Cquad%20x%3D3%5C%5C%5C%5C%5Cmathrm%7BFor%5C%3A%7Dx%5Cge%20%5C%3A12%3A%5Cquad%20%5Cmathrm%7BNo%5C%3ASolution%7D%5C%5C%5C%5C%5Cmathrm%7BCombine%5C%3ASolutions%3A%7D%5C%5C%5C%5C%5Cmathrm%7BNo%5C%3ASolution%7D%5Cquad%20%5Cmathrm%7Bor%7D%5Cquad%20%5C%3Ax%3D3%5C%5C%5C%5Cx%3D3)
Answer:
Option C is correct
Step-by-step explanation:
The common difference is 10,
So, the function is f(n + 1) = f(n) + 10 , where f(1) = 14
The recursive function for the arithmetic sequence is given by:
.....[1]
where d is the common difference of the two consecutive terms.
Given the arithmetic sequence :
14, 24, 34, 44, 54, .......
First term f(1) = 14
Common difference(d) = 10
Since,
24 -14 = 10
34-24 = 10
44-34 = 10 and so on....
Substitute d = 4 in [1], we have;
Therefore, the recursive function used to generate the sequence is,
and f(1) = 10
Answer: i believe jts -13 or 13
Step-by-step explanation: